Repeated exposure and conditioning strategies for increasing vegetable liking and intake: systematic review and meta-analyses of the published literature. Issue 4 (12th October 2018) - Appleton, Katherine M; Hemingway, Ann; Rajska, Jessica; Hartwell, Heather
Abstract: Background: Vegetable intakes are typically lower than recommended for health. Although repeated exposure has been advocated to increase vegetable liking and consumption, no combination of the evidence yet provides a measure of benefit from repeated exposure or alternative conditioning strategies. Objective: This work aimed to identify and synthesize the current evidence for the use of repeated exposure and conditioning strategies for increasing vegetable liking and consumption. Design: Three academic databases were searched over all years of records using prespecified search terms. Published data from all suitable articles were tabulated in relation to 3 research questions and combined via meta-analyses. Results: Forty-three articles detailing 117 comparisons investigating the use of repeated exposure and conditioning strategies for increasing liking and intakes of vegetables were found. Our analyses demonstrate: 1) increased liking and intakes of the exposed vegetable after repeated exposure compared with no exposure; 2) increased liking for the exposed vegetable after conditioning compared with repeated exposure, increased intakes after the use of rewards, and some suggestion of decreased intakes after flavor-nutrient conditioning; and 3) increased liking and intakes of a novel vegetable after repeated exposure to a variety of other vegetables compared with no exposure or repeated exposure to one other vegetable. Effect sizes, however, are small, and limited evidence suggests long-term benefits. Our analyses, furthermore, are limited by limitations in study design, compliance, and/or reporting. Conclusions: Based on our findings, we recommend the use of repeated exposure to one and a variety of vegetables, and the use of rewards, for increasing vegetable liking and consumption. Confirmation from further large, well-conducted studies that use realistic scenarios, however, is also required. This study was registered at PROSPERO as CRD42017056919.